Kepemimpinan Dan Disiplin Kerja Sebagai Variabel Berpengaruh Pada Kinerja Karyawan Cv. Kurnia Alam Sejahtera - Siregar, Fikri Arizal; Sarwoto, Sarwoto; Purba, Rakhmawati (Economic Development Progress, 2022)
The research was conducted on 31 employees of CV. Kurnia Alam Sejahtera in Tebing Tinggi City. The limited number of employees is able to achieve the company's target and the company becomes stable. Accepted leadership and employee discipline are interesting things to research on the object. The quantitative approach becomes interesting to answer the alleged hypothesis supported by SPSS 25.00. The results of the study answer the positive and unidirectional influence between the independent variable and the dependent variable.